LES EFFORTS DE SIMION MEHEDINŢI POUR RENDRE LA ROUMANIE MIEUX CONNUE AU-DELÀ DES FRONTIÈRES - ALEXANDRU UNGUREANU (Revue Roumaine de Géographie)
Simion Mehedinţi’s efforts in order to make Romania better known for the foreigners. Especially in the years between the two world wars, one of the Simion Mehedinţi’s main preoccupations was the very low level of knowledge about the geography and the history of Romania, not only among the ordinary people of the other countries but even in the circles of the better educated citizens. Mehedinţi’s activity in order to improve this situation can be subdivided into three periods. The first one was that of the beginnings, based on some field researches and on the analysis of the very fine Romanian first topographic maps; the best known of the works of this period is Die rumänische Steppe, eine anthtropogeographische Skizze, published in Leipzig in 1904. The second period was that of the maturity stage, when he published very seriously documented works, like Der Zusammenhang der rumänischen Landschaft mit dem rumänischen Volke, where the author underlines four main characteristics of this country and of its people – the marginality of the country and of its population in the European continent, the isolation of the Romanians as a consequence of the great migrations, the linguistic and ethnic homogeneity of the Romanians and the archaic characteristics of the Romanian civilization. Finally, in the third period author’s efforts, displayed in books translated in foreign languages, like Romania and its people, have been directed towards the defence of the national rights, demonstrating especially the inequity of the political frontiers imposed to Romania in 1940.